TINJAUAN YURIDIS PEMIDANAAN TERHADAP PELAKU PENYALAHGUNA NARKOTIKA GOLONGAN I (STUDI PUTUSAN NOMOR 132/PID.SUS/2022/PN BTM) - Oemyx Wynn Tratabofa Hutasoit; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: As a developing country, Indonesia has become one of the targets as a place to produce and distribute narcotics, which until now the amount of drug abuse in Indonesia has been very high, including the cases experienced by defendants in narcotics crimes in the criminal case against perpetrators of criminal narcotics abusers I. The main problem is How to Punishment Against Narcotics Abusers Group I and Judge's Considerations Against Narcotics Offenders. This research is a normative research based on Decision No. 132/PID.SUS/2022/PN. Btm. Data analysis was carried out qualitatively and conclusions were drawn using deductive logic, based on the analysis that had been carried out on Convicts of Class I Narcotics Abusers that the defendant's actions fulfilled the elements of Article 127 Paragraph (1) of Law Number 35 of 2009, in imposing a sentence against perpetrators of Narcotics or Narcotics Abuse for themselves, the judge must pay attention to SEMA No. 4 of 2010 in the imposition of sanctions for the actions of Jefri Sagita bin Imron, namely providing Rehabilitation sanctions as one of the efforts to prosecute perpetrators who are victims of Narcotics abuse and not impose prison sentences.Keywords: Crime of Narcotics Abuse.